Eksplorasi Konsep Geometri pada Rumah Adat Bugis Saoraja di Kabupaten Pinrang - Selpiana (Journal of Mathematics Learning Innovation, 2024)
Ethnomathematics serves as a bridge between abstract mathematics and culturally relevant contexts for students, enabling them to observe the application of mathematical concepts in everyday life, traditions, and local knowledge. This study aims to identify the geometric concepts found in the Bugis traditional house Saoraja Sawitto, understand the philosophical meanings embedded in its architectural forms, and design a geometry learning pathway. The research employs a qualitative ethnographic approach, utilizing data collection techniques such as observation, interviews, and documentation. Data analysis is conducted using domain and taxonomy analysis methods. The findings reveal the presence of geometric concepts in the Bugis Saoraja Sawitto house, encompassing plane geometry (triangles, squares, rectangles, circles, trapezoids, and rhombuses) as well as solid geometry (pyramids, cubes, rectangular prisms, cylinders, and prisms). Several architectural elements possess profound philosophical meanings, such as the Indisch architectural style reflecting the status and power of Dutch colonialism, the colors yellow and green representing the nobility, and the triangular and rectangular carvings symbolizing power, glory, and the number of Ajatappareng. These findings can serve as a contextual learning resource in mathematics education within formal settings by creating a relevant learning pathway and implementing it in the classroom.